Anomalous V2 of the left pulmonary vein detected using three-dimensional computed tomography in a patient with lung cancer: A case report. (2017) - Aragaki, Masato; Iimura, Yasuaki; Yoshida, Yusuke; Hasegawa, Naoto
Highlights: We report the rare anatomical variations of the pulmonary vein wherein the left V2 drained into the inferior pulmonary vein. The left V2 draining into the inferior pulmonary vein has not been yet reported, and this case is the first report. We identify this anomalous V2 before operation by 3D-CT and were able to perform the operation safely by VATS. Abstract: We report one of the rare anatomical variations of the pulmonary vein wherein the left V2 drained into the inferior pulmonary vein. A 63-year-old man was referred to our hospital because of an abnormal shadow in the left lower lung field that was noted on chest X-ray. Computed tomography (CT) revealed a tumor in the left lower lobe. A biopsied tumor specimen was diagnosed as an adenocarcinoma, and thus, left lower lobectomy was performed. Preoperative three-dimensional CT revealed that an anomalous V2 of the left lung drained from the superior segment into the inferior pulmonary vein. This variation type was confirmed during thoracoscopic left lower lobectomy. We were able to perform left lower lobectomy with the preservation of the anomalous V2. The postoperative course was uneventful, and the patient was discharged on postoperative day 12. It is important to identify anatomical variations of the pulmonary vein and reliably preserve and process the affected area to prevent postoperative complications.